2002
DOI: 10.1002/jcb.10113
|View full text |Cite
|
Sign up to set email alerts
|

Reduced CpG methylation is associated with transcriptional activation of the bone‐specific rat osteocalcin gene in osteoblasts*

Abstract: Chromatin remodeling of the bone-specific rat osteocalcin (OC) gene accompanies the onset and increase in OC expression during osteoblast differentiation. In osseous cells expressing OC, the promoter region contains two nuclease hypersensitive sites that encompass the elements that regulate basal tissue-specific and vitamin D-enhanced OC transcription. Multiple lines of evidence indicate that DNA methylation is involved in maintaining a stable and condensed chromatin organization that represses eukaryotic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 32 publications
4
68
1
Order By: Relevance
“…Considering these findings, the methylation-associated silencing of the ChM-I gene in OBOS and FBOS might be a transformation-related phenomenon. However, it also is likely that the silencing of the ChM-I gene is a physiological phenomenon occurring during the differentiation of mesenchymal cells as demonstrated for other genes (33)(34)(35). We showed that the removal of methylation restored the binding of Sp3 and induced the expression of the ChM-I gene in osteoblastic cells (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Considering these findings, the methylation-associated silencing of the ChM-I gene in OBOS and FBOS might be a transformation-related phenomenon. However, it also is likely that the silencing of the ChM-I gene is a physiological phenomenon occurring during the differentiation of mesenchymal cells as demonstrated for other genes (33)(34)(35). We showed that the removal of methylation restored the binding of Sp3 and induced the expression of the ChM-I gene in osteoblastic cells (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…P2X 7 mRNA and protein receptor levels are lower in cancer cervical cells than in normal cells, both in culture and in vivo [7,[11][12][13], while CpG sites +211/+212, +330/+331, and +461/+464 were hypermethylated in the cancer cervical cells compared to the normal cells (present data). In other systems, hypermethylation of genes has been associated with repression of tumor suppressor genes [60], and has been implicated in cancer development and metastasis [51,56,61,62]. DNA hypermethylation in the promoter [51] or in 5′ non-coding or coding regions [52,57,58] can lead to defects in DNA repair, cell cycle control, cell adherence, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This hypermethylation was confirmed to be associated with a condensed chromatin structure (Villar-Garea and Esteller, 2004). Subsequent experiments have revealed that CpG methylation of the osteocalcin promoter region diminishes during in vitro osteoblastic differentiation of MSCs (Villagra et al, 2002). After differentiation by mechanical stimulus, upregulation of bone-specific genes has been found to be due to reduced CpG methylation of the genes (Arnsdorf et al, 2010;Karakaş et al, 2014).…”
Section: Dna Methylation In Osteogenic Differentiationmentioning
confidence: 96%